Determinants of Dividend Policy on Development Board Index: Manufacturing Sector in Indonesia Stock Exchange (IDX) - Resti Aulia Safitri; Sri Dwi Ari Ambarwati; Aryono Yacobus (Management Research Studies Journal, 2023)
This study aims to investigate the determinant factors that affect dividend policy in Development Board Index  (DBX), with the manufacturing sector listed in Indonesia stock exchange (IDX) and the period 2018-2021. There are independent variables such as ROA, debt, sales growth and firm age and dividend policy as dependent variables. The study population are manufacturing companies which are listed on the development board index. This study examines 8 companies with a total of 32 data samples. The panel data regression with random effect model was used to analyze data. The results of this study are ROA, and sales growth has an impact on dividend policy. ROA has a positive impact, and sales growth has a negative impact on dividend policy. Meanwhile, debt and age have no significant impact on the dividend policy.   Keywords: Development Board Index, Dividend Policy, Profitability, Debt, Sales Growth